Samoa : Report on Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This report reviews the Observance of Standards and Codes on the Fiscal Transparency Module for Samoa. The assessment reveals that as a result of reforms over a number of years, Samoa has made substantial progress in improving fiscal transparency and now meets the standards in the Fiscal Transparency Code in a significant number of areas. There is a comprehensive and modern legal framework for fiscal management. The central bank has effective independence. The budget is comprehensive and reliable, the public accounts are timely and comprehensive, and there is quite extensive reporting of noncash items.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet